(3GdOQI GdKejfI aj CNHGQ GdeOjfIs - (3GHf GdfLGQ , eMeO Hf eMehO Hf GdMSf Hf gHI Gddg Hf eMGSf, eMH GdOjf CHh YHO Gddg,J (B643 (3g` s ((3CMeO GdCfbQhi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO aEfi deG ONdJ eOjfI GdfHi Udi Gddg Ydjg hSde hGSYOJ HRjGQJg CbeJ HgG aGLJeYJ HLGeYI ef Cgd GdUdGM hGdYde hGdaVd aSCdhfi aVGFd GdeOjfI hCNHGQgG aCNHQJge ajeG JYdb HNGWQi s
(3BNQgG (B:s
(3HfhG YbHI CUMGH GdCNHGQ eMeO Hf ESMb Hf jSGQ eGdc Hf CfS GdEeGe jhSa CHh GdeGLThf JeJ JGQjN GdeOjfI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B86 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B317s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B739s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs